2022
DOI: 10.2196/29045
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Hepatobiliary and Pancreatic Surgical Services in Singapore: Retrospective Quantitative Study

Abstract: Background At the height of the COVID-19 pandemic, the hepatopancreatobiliary (HPB) unit had to reorganize its surgical case volume due to the rationing of health care resources. We report on a local audit evaluating the impact of COVID-19 on the HPB unit and the HPB surgical oncology practice. Objective The aim of this study was to review the impact of the COVID-19 pandemic on the HPB unit’s elective and emergency surgical cases. The secondary aims wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
(15 reference statements)
0
8
0
Order By: Relevance
“…Thus, knowledge of COVID-19 as an aetiology of AP is important as it stops the pursuit of aetiology identification, guides physician on the counselling of their patients, and impacts management decision for cholecystectomy. In patients with mild biliary pancreatitis, index admission laparoscopic cholecystectomy is considered good clinical practice while surgery should be delayed in patients with COVID-19 infection to minimize risk to healthcare workers and reduce patient morbidity[ 93 , 94 ]. Shao et al [ 95 ] analysed 589 patients with COVID-19 infection prior to surgery and concluded that postoperative mortality was nearly 6 times higher for patients infected with COVID-19 within 2 wk before surgery when adjusting for patient and procedure level factors[ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, knowledge of COVID-19 as an aetiology of AP is important as it stops the pursuit of aetiology identification, guides physician on the counselling of their patients, and impacts management decision for cholecystectomy. In patients with mild biliary pancreatitis, index admission laparoscopic cholecystectomy is considered good clinical practice while surgery should be delayed in patients with COVID-19 infection to minimize risk to healthcare workers and reduce patient morbidity[ 93 , 94 ]. Shao et al [ 95 ] analysed 589 patients with COVID-19 infection prior to surgery and concluded that postoperative mortality was nearly 6 times higher for patients infected with COVID-19 within 2 wk before surgery when adjusting for patient and procedure level factors[ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data from several studies provides evidence for the decrease in the number of surgeries for cholelithiasis during the COVID-19 pandemic. Teo et al (2022), conducted in Singapore, aimed to analyze the volume of surgical interventions in the specialized hepatobiliary department while comparing the periods from January to June of 2019 and 2020 (the first wave of COVID-19), the number of cholecystectomies decreased by 40.1%. Patel et al (2022) in a retrospective cohort study of adult patients presented to the emergency department with symptoms related to gallstone disease during the pandemic concluded that older patients with higher comorbidity presented with acute gallstone disease.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…In response to the pandemic, many surgeries were postponed or canceled due to COVID-19, especially surgery for the pancreas[ 27 ]. Elective surgery decreased by 41.8% compared to 2019, including hernial surgery (63.9% decrement), cholecystectomy (40.1% decrement), liver surgery (16.7% decrement), and pancreatic surgery (111.1% decrement) in Singapore[ 27 ].…”
Section: Surgical Interventions For Covid-19-related Apmentioning
confidence: 99%
“…In response to the pandemic, many surgeries were postponed or canceled due to COVID-19, especially surgery for the pancreas[ 27 ]. Elective surgery decreased by 41.8% compared to 2019, including hernial surgery (63.9% decrement), cholecystectomy (40.1% decrement), liver surgery (16.7% decrement), and pancreatic surgery (111.1% decrement) in Singapore[ 27 ]. A study from ten Italian referral centers ( n = 1423) reported a 18.7% decrement in the surgical volume in 2020, with a 43.4% decrease in surgery for benign lesions and a decrease of 33.6% in operations for neuroendocrine tumors[ 28 ].…”
Section: Surgical Interventions For Covid-19-related Apmentioning
confidence: 99%